Bridging the Digital Divide: A Narrative Review of Teacher Professional Development in the 21st Century - Anisah, Ani Siti; Siti, Sopa; Holis, Ade (Sinergi International Journal of Education, 2024)
The rapid digitalization of education has placed new demands on teacher competence and institutional support systems. This narrative review aims to synthesize empirical evidence on digital competence development among teachers and analyze the systemic factors that influence the success of training programs. A structured literature synthesis was conducted across peer-reviewed sources focusing on digital readiness, training models, infrastructure, and policy frameworks. Findings reveal significant disparities in digital competence influenced by teacher age, region, and educational level. Teachers in urban settings generally demonstrate higher digital skills due to better infrastructure and support. Systemic barriers such as limited funding, rigid organizational structures, and inadequate policy backing contribute to uneven training outcomes. However, programs that integrate technical, pedagogical, and content knowledge (TPACK), with sustained mentoring and reflective practices, show considerable promise in improving digital integration. School culture and leadership further impact teacher confidence, with collaborative environments promoting innovation. This study underscores the urgency of reforming digital training strategies through inclusive and adaptive models that address both technical and emotional aspects of teaching in the digital era. Policy recommendations include expanding access to infrastructure, enhancing mental health support, and investing in hybrid and personalized professional development. The findings contribute to global discourse on education reform and provide a roadmap for bridging the digital divide in diverse learning environments.